Legal Protection For Creditors In Fiduciary Guarantee Agreements In Indonesia - Heddy Kandou; Wiwik Sri Widiarty (International Journal of Artificial Intelligence Research, 2022)
A fiduciary guarantee is one of the material guarantees known in positive law to carry out the function of a bank or creditor running its business, providing credit to its customer or debtor, and offering credit by the bank (the creditor) to its customer (the debtor), based on the ability and ability of the debtor to take debt advantage. In providing credit to customers (debtors), of course, there are conditions of a guarantee that must meet by debtors. There are problems from the results of the explanation, among others, first, legal protection for creditors in the fiduciary guarantee agreement, and second, the arrangement of fiduciary guarantee rights holders. This study uses a normative legal research method, which focuses on library studies, and this research uses a Legislation approach and is descriptive of qualitative analysis. Then from the first results, legal protection for the interests of creditors as fiduciaries is to provide definite provisions for creditors and complete data arrangements that must include in the fiduciary guarantee. Second, the performance of fiduciary rights holders in Indonesia, contained in Book II of the Civil Code, Law Number 42 of 1999 concerning Fiduciary Rights, and Law Number 4 of 1996 concerning Mortgage Rights